TRANSFORMATION OF DIGITAL-BASED CHRISTIAN RELIGIOUS EDUCATION LEARNING MEDIA: A Descriptive Study of the Alpha Generation at SMP Negeri 2 Sentani - Mano, Selvia Everlline Joice; Pandi, Seprianti Elisabet; Malatuny, Yakob Godlif (JUPE : Jurnal Pendidikan Mandala, 2025)
This research aims to describe the transformation of digital-based Christian Religious Education learning for Alpha Generation students. The background of this research is the gap between the rapid advancement of digital technology and the conventional approach to religious learning. The research used a qualitative method with a descriptive design. The research subjects consisted of students and teachers. Data were collected through observation, interviews, and documentation, then analysed using thematic analysis techniques. The results showed that the integration of digital media in Christian Religious Education learning contributed to increasing students' interest in learning, participation, and understanding. Digital media is perceived as more interactive, relevant, and in accordance with the characteristics of Generation Alpha. However, this study also found barriers in the form of limited school facilities and teachers' readiness in mastering technology. Overall, this study confirms that digital-based learning innovation is a significant strategy to improve the quality of Christian Religious Education in the digital era